The Essence Of Artificial Intelligence
The Essence of Artificial Intelligence provides a concise and accessible introduction to the topic for students with no prior knowledge of AI. Taking a pragmatic approach to the subject, this book de-mystifies and makes AI concrete and transparent. Examples and algorithms are given throughout and can be sensibly implemented in a range of different languages. Offering a less formal/ mathematical treatment of the subject than many of its competitors, The Essence of Artificial Intelligence provides an overview of all the key subjects covered in one semester.